Creating a functional additive BC-P - Даниленко, Світлана Григорівна (Technology audit and production reserves, 2014)
Creation of the functional additive BC-P for using in veterinary is considered in the paper. Some results of our research in this field are given. The main purpose of the research is to create a functional additive in selecting the ratio between strains according to the spectrum of antagonistic activity of a number of pathogens that cause diseases in the porcine gastrointestinal tract. For this purpose, it was necessary to determine the type of relationship between the strains of lactobacilli and bifidobacteria under study, and the ability to general growth in mixed cultures using the indicators of acid formation and accumulation of viable cells of each of the component composition is tested. In this paper, the optimum ratio between the strains during co-cultivation is determined. The presented method allows creating a functional additive based on the strains of Bifidobacterium infantis: B. longum subsp. suis: Lactobacillus acidophilus: L. with maximum antagonistic effect on a number of pathogens. The research results can be used by researchers to create probiotic preparations both for people and animals, as well as to create bacterial preparations for fermented meat and dairy products.